Dietary fucoidan supplementation in black tiger shrimp (Penaeus monodon) enhances immune response and resistance against WSSV and VP AHPND - Faisan, Joseph Polido Jr
Fucoidan-containing kelp powder from Durvillaea potatorum supplemented diets (control, 1, 2.5 and 5 g kg-1) were experimentally fed to blavk tiger shrimp (Penaaeus monodon) for 30 days and subsequently challenged with white spot syndrome virus (WSSV) and EMS/ AHPND causing Vibrio arahaemolyticus (VPAHPND) pathogens. Growth, survival and immunologicalindices (total hemocyte count, differential hemocyte count, phenoloxidase activity, plasma (pH>2) is compound on these physiological responses. The results of the challengeexperiments for both WSSV and VPAHPND revealed that at 5 g kg-1 fucoidan supplementation, survival rates compared with the control group. Also, treatments with fucoidan inclusion in the diet exhibited higher immunological response compared with the unsupplemented group. treatments. The results of this study demonstrated that supplementation in the diet of fucoidan derived from D. potatorum activated the shrimp's immune response and it effectively developed resistance against WSSV and VP AHPND at 5 g kg-1 fucoidan supplementation.